2015
DOI: 10.3923/ajb.2015.306.311
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Chronic Esculetin (6,7-Dihydroxy-Coumarin)-Induced Alteration in Some Haematological and Serum Parameters in Normal Male Wistar Rats

Abstract: The sub chronic esculetin (6,7-dihydroxy-coumarin)-induced response on malondialdehyde concentration and some haematological and lipid metabolism parameters was studied in normal male Wistar rats to further understand the underlying esculetin metabolism and effects. Five groups (n = 6) of rats, A-E were respectively exposed to 6.0, 12.0 and 24.0 mg kgG ) decreased (p<0.05) but increased numerically with increasing dose. Thus, the sub-chronic esculetin-induced alteration was inversely related to esculetin dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In particular, the observation and the bio-consequence could be overriding in the liver of rats concomitantly exposed to AL overdose and MSG. Prevailing MDA concentration in biologic sample could be diagnostic [48]. Cellular and tissue proteins-related malondialdehyde adduct formation could result in protein dysfunction and attendant alteration in cellular responses [29,49].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the observation and the bio-consequence could be overriding in the liver of rats concomitantly exposed to AL overdose and MSG. Prevailing MDA concentration in biologic sample could be diagnostic [48]. Cellular and tissue proteins-related malondialdehyde adduct formation could result in protein dysfunction and attendant alteration in cellular responses [29,49].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the present study, MSG intoxication caused a significant (p<0.05) reduction in WBC counts in the rats as compared to control [10,53] , indicating inconsistent adverse response on the WBC of rats exposed to intoxicating concentration of MSG. The implication of altered immune response following reduced WBC count have been reported [59][60][61] , thus further studies are warranted to determine the basis for the high WBC count observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hydroxycoumarin scopoletin (6-methoxy-7-hydroxycoumarin), which represents major phytoalexins in tobacco plants, elicited antimicrobial activity [4][5][6] and in rats even improved serum bio-indicators of varied organs functions in rats. [10][11][12] Currently, phytoalexins are utilized as antibiotic potentiators. 13,14 A good example is epigallocatechingallate which potentiated the activity of β-lactam antibiotics against methicillin-resistant Staphylococcus aureus (MRSA) by mechanisms involving binding of the catechin in the bacterial wall.…”
Section: Phytoalexins As Antimicrobial Agentsmentioning
confidence: 99%